Two periods instead of one in a single 6.7 GHz methanol maser feature in G9.62+0.20E. Issue 1 (2nd August 2022) - MacLeod, G C; Yonekura, Y; Tanabe, Y; Baan, W A; Brogan, C L; Burns, R A; Chibueze, J O; Houde, M; Hunter, T R; Kurtz, S E; Rajabi, F; Smits, D P; et al.
ABSTRACT: The source G9.62+0.20E surprises yet again! Analysis of the associated methanol maser feature at v lsr = +8.8 km s −1 revealed a second period of P = 52.1 ± 0.3 d, along with the previously reported period P = 243 d for this source. Various explanations, harmonic flaring, Dicke's superradiance, a secondary pulsation, or two different periodically varying radio sources in the field of view with associated methanol masers are presented. The latter two hypotheses appear more plausible but it is not clear which, if any, best describe these observations.